Avoiding ambient air and light induced degradation in high-efficiency polymer solar cells by the use of hydrogen-doped zinc oxide as electron extraction material. (April 2017) - Polydorou, Ermioni; Sakellis, Ilias; Soultati, Anastasia; Kaltzoglou, Andreas; Papadopoulos, Theodoros A.; Briscoe, Joe; Tsikritzis, Dimitris; Fakis, Mihalis; Palilis, Leonidas C.; Kennou, Stella; Argitis, Panagiotis; Falaras, Polycarpos; et al.
Abstract: Polymer solar cells have undergone rapid development in recent years. Their limited stability to environmental influence and during illumination, however, still remains a major stumbling block to the commercial application of this technology. Several attempts have been made to address the instability issue, mostly concentrated on the insertion of charge transport interlayers in the device stack. Although zinc oxide (ZnO) is one of the most common electron transport materials in those cells, the presence of defects at the surface and grain boundaries significantly affects the efficiency and stability of the working devices. To address these issues, we herein employ hydrogen-doping of ZnO electron extraction material. It is found that devices based on photoactive layers composed of blends of poly(3-hexylthiophene) (P3HT) with electron acceptors possessing different energy levels, such as [6, 6]-phenyl-C70 butyric acid methyl ester (PC70 BM) or indene-C60 bisadduct (IC60 BA) essentially enhanced their photovoltaic performance when using the hydrogen-doped ZnO with maximum power conversion efficiency (PCE) reaching values of 4.62% and 6.65%, respectively, which are much higher than those of the cells with the pristine ZnO (3.08% and 4.51%). Most significantly, the degradation of non-encapsulated solar cells when exposed to ambient or under prolonged illumination is studied and it is found that devices based on un-doped ZnO showed poor environmental stability and significant photo-degradation while those using hydrogen-doped ZnO interlayers exhibited high long-term ambient stability and maintained nearly 80–90% of their initial PCE values after 40 h of 1.5 AM illumination. All mechanisms responsible for this enhanced stability are elucidated and corresponding models are proposed. This work successfully addresses and tackles the instability problem of polymer solar cells and the key findings pave the way for the upscaling of these and, perhaps, of related devices such as perovskite solar cells. Graphical abstract: Hydrogen-doping of ZnO significantly boosts the efficiency while simultaneously strengthens the stability of polymer solar cells. Stemming from synergistic effects, the hydrogen-doped ZnO electron extraction material offers several advantages over its un-doped counterpart including less density of surface traps and defects at grain boundaries followed by removal of adsorbed oxygen species, more efficient charge separation and better electron extraction/transport capability. Highlights: Hydrogen-doping of zinc oxide electron extraction material boosts the performance of polymer solar cells. Superior long-term stability and photostability of non-encapsulated devices with hydrogen-doped zinc oxide layers. Passivation of defects at surface and grain boundaries of zinc oxide via hydrogen-doping. Enhanced exciton dissociation and suppressed recombination losses in hydrogen-doped zinc oxide /organic interfaces. Improved electron selectivity of hydrogen-doped zinc oxide material.